Microstructural and mechanical characterization of stir cast Al-SiC/Flyash/Graphite hybrid metal matrix composite. (2022) - Chechi, Prashant; Maurya, Saurabh Kumar; Prasad, Rabindra; Manna, Alakesh
Abstract: Aluminium is one of the most commonly used material in manufacturing industries. Hybrid aluminium matrix composite have recently received a lot of attention recently in the aviation, aerospace, and automotive industries to meet the advance engineering challenges. The present study focus on fabricating aluminium metal matrix hybrid composites using AA6061 as a matrix material and a novel combination of Silicon Carbide (SiC), Flyash and Graphite (Gr) as reinforcing materials by employing stir casting process. Mechanical properties like yield strength, ultimate tensile strength, percentage elongation and hardness were evaluated for the developed composite specimens in accordance with ASTM standards. The metallography of the developed composite was assessed by using optical microscope and scanning electron microscope (SEM). The fabricated composite disclosed fine grain structure as compared to the as cast aluminium alloy. The hardness of developed composite increased due to the presence of brittle and hard reinforcement particles into the matrix material. The developed composite has a higher tensile strength which may be attributed to the load transmission from the matrix material to the reinforcing particles.